2011
DOI: 10.1111/j.1468-3083.2011.04204.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis herpetiformis in China: a report of 22 cases

Abstract: The clinical, histological and immunopathological characteristics of Chinese patients with DH are similar to those seen in Caucasian populations. The positive rates of anti-EMA and anti-tTG antibodies were lower compared with those seen in Western countries. DH is not extremely rare in China and should be actively investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 33 publications
(58 reference statements)
5
33
2
1
Order By: Relevance
“…Additionally, it is accepted that all DH patients have CD in theory, due to sharing a common mechanism, even though they usually have subclinical gastrointestinal disease and only mild symptoms. In our DH patients, 37.5% were diagnosed with CD by histopathological examination, whereas this was reported as 3.3%-18% in the literature (13,22).…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Additionally, it is accepted that all DH patients have CD in theory, due to sharing a common mechanism, even though they usually have subclinical gastrointestinal disease and only mild symptoms. In our DH patients, 37.5% were diagnosed with CD by histopathological examination, whereas this was reported as 3.3%-18% in the literature (13,22).…”
Section: Discussioncontrasting
confidence: 40%
“…In spite of reports that cardiovascular diseases were generally associated with BP, cardiovascular diseases were also associated with other ABDs in some case reports (13,22,24). Nevertheless, Marzano at al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study of 22 patients with dermatitis herpetiformis, the authors searched for IgA antibodies against endomysial antigen (EmA) and tTG and only found these antibodies in 50% and 62.5% of their sera, respectively. Small intestinal biopsies confirmed the presence of celiac disease in only two patients [5]. Pruritus is the predominant DH symptom; the eruption is symmetric, with a predilection for the shoulders, buttocks, elbows, and thighs and extensor areas [1].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, we used sodium dodecyl sulfate (SDS) extracts of human and bovine epidermis fractionated by 7% SDS polyacrylamide gel electrophoresis (SDS-PAGE) according to the Laemmli method [9,10,14]. Gels were transferred onto nitrocellulose membranes (5,10). As experimental controls, we utilized 1) an anti-desmoplakin multiepitope cocktail from Progen (Heidelberg, Germany), 2) the serum of a patient with bullous pemphigoid that recognized bullous pemphigoid antigens 1 and 2 (230 and 180 kDa, respectively), and 3) serum from a patient with paraneoplastic pemphigus.…”
Section: Immunoblotting (Ib)mentioning
confidence: 99%